Exchange rate and central bank intervention - Wong, Hock Tsen (OMICS International, 2014)
Exchange rate and central bank intervention is an important topic in the exchange rate determination [1-4]. Exchange rates are volatile after the breakdown of the Bretton Woods system of fixed exchange rate in the year 1973. Central banks especially those in economies adopted a managed exchange rate regime actively intervene in the exchange rate market to maintain their exchange rates and to reduce their exchange rate volatility, which can affect international trade, financial flow and economic growth. Central bank intervention in the exchange rate market may want to accrue international reserves to enhance the fundamental of the economy [5]. There are two important issues related to the exchange rate intervention, namely the effectiveness of central bank intervention and the success of central bank in maintaining the exchange rate and in reducing exchange rate volatility [1,4,6]. In general, the literature of exchange rate and central bank intervention is inconclusive on the impact of central bank intervention. Most studies conclude that central bank intervention tends to increase exchange rate volatility.